Therapeutic Effects of Curcumin Derivatives against Obesity and Associated Metabolic Complications: A Review of In Vitro and In Vivo Studies - Moetlediwa, Marakiya T.; Ramashia, Rudzani; Pheiffer, Carmen; Titinchi, Salam J. J.; Mazibuko-Mbeje, Sithandiwe E.; Jack, Babalwa U. (International journal of molecular sciences, 2023)
Obesity is a major cause of morbidity and mortality globally, increasing the risk for chronic diseases. Thus, the need to identify more effective anti-obesity agents has spurred significant interest in the health-promoting properties of natural compounds. Of these, curcumin, the most abundant and bioactive constituent of turmeric, possesses a variety of health benefits including anti-obesity effects. However, despite its anti-obesity potential, curcumin has demonstrated poor bioavailability, which limits its clinical applicability. Synthesizing curcumin derivatives, which are structurally modified analogs of curcumin, has been postulated to improve bioavailability while maintaining therapeutic efficacy. This review summarizes in vitro and in vivo studies that assessed the effects of curcumin derivatives against obesity and its associated metabolic complications. We identified eight synthetic curcumin derivatives that were shown to ameliorate obesity and metabolic dysfunction in diet-induced obese animal models, while five of these derivatives also attenuated obesity and associated metabolic complications in cell culture models. These curcumin derivatives modulated adipogenesis, lipid metabolism, insulin resistance, steatosis, lipotoxicity, inflammation, oxidative stress, endoplasmic reticulum stress, apoptosis, autophagy, fibrosis, and dyslipidemia to a greater extent than curcumin. In conclusion, the findings from this review show that compared to curcumin, synthetic curcumin derivatives present potential candidates for further development as therapeutic agents to modulate obesity and obesity-associated metabolic complications.